Peran End Child Prostitution in Asian Tourism (ECPAT) Indonesia Dalam Isu Eksploitasi Seksual Komersial Anak Berbasis Elektronik di Indonesia Tahun 2017-2022 - Pranata, Nyoman Gede Widaraditya Giri; Parameswari, Anak Agung Ayu Intan; Sushanti, Sukma (DIKSHI (DISKUSI ILMIAH KOMUNITAS HUBUNGAN INTERNASIONAL); Vol 4 No 4 (2025): JURNAL DIKSHI, 2025)
The issue of electronic-based commercial sexual exploitation of children (CSEC) is a new threat to the welfare of Indonesian children. Moreover, the increasing intensity of internet use in people's daily lives not accompanied by knowledge regarding digital literacy can increase the potential for children to become victims of this issue. The purpose of this research is to explain the actions taken by ECPAT Indonesia as one of the International Non-Governmental Organizations (INGO) which focuses on this issue. To analyze this, researchers used descriptive-qualitative research methods and the concepts of commercial sexual exploitation of children, digital literacy, and also the role of INGOs, namely service delivery, catalyst, and partnership as analytical tools. This research found that ECPAT Indonesia carried out the role of INGO as a service delivery on this issue by providing education related to digital literacy and electronic-based ESKA to increase public understanding of this phenomenon. Furthermore, ECPAT Indonesia also plays its role as a catalyst through its efforts to advocate for this issue by releasing research "Disrupting Harm in Indonesia" which collects new data and facts related to this policy or issue. Lastly, ECPAT Indonesia also carries out its function in partnership by collaborating with Internet Watch Foundation.